let f, g be Function of (REAL-NS n),(REAL-NS 1); :: thesis: ( ( for x being Point of (REAL-NS n) holds f . x = <*((proj (i,n)) . x)*> ) & ( for x being Point of (REAL-NS n) holds g . x = <*((proj (i,n)) . x)*> ) implies f = g )

assume that

A3: for x being Point of (REAL-NS n) holds f . x = <*((proj (i,n)) . x)*> and

A4: for x being Point of (REAL-NS n) holds g . x = <*((proj (i,n)) . x)*> ; :: thesis: f = g

assume that

A3: for x being Point of (REAL-NS n) holds f . x = <*((proj (i,n)) . x)*> and

A4: for x being Point of (REAL-NS n) holds g . x = <*((proj (i,n)) . x)*> ; :: thesis: f = g

now :: thesis: for x being Point of (REAL-NS n) holds f . x = g . x

hence
f = g
by FUNCT_2:63; :: thesis: verumlet x be Point of (REAL-NS n); :: thesis: f . x = g . x

f . x = <*((proj (i,n)) . x)*> by A3;

hence f . x = g . x by A4; :: thesis: verum

end;f . x = <*((proj (i,n)) . x)*> by A3;

hence f . x = g . x by A4; :: thesis: verum